Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Berpikir Kritis Peserta Didik - Lia Nurmayani; Aris Doyan; Ni Nyoman Sri Putu Verawati (Department of Physics Education, Universitas Mataram, 2018)
This study aims to determine the effect of guided inquiry learning model toward critical thinking skills of students. This type of research is quasi experiment with non-equivalent group design. Sampling using purposive sampling technique, so that obtained class XI MIA 1 as experiment class and class XI MIA 2 as control class. The research instrument is a essay test of 5 questions that have been tested for validity, reliability, level of difficulty, and different power of problems. The learning data of the two classes is normally distributed. Based on the homogenity data obtained both homogeneous. Data were analyzed by MANOVA test. Result of data analysis show significanceÃÂ 0,021 ifÃÂ determined the level of significance 0,05 then 0,021<0,05. Based on these facts it can be concluded that there is influence of guided inquiry learning model toward critical thinking skills of students.